ANALISIS SWOT SDM GURU DALAM MENGHADAPI IMPLEMENTASI KURIKULUM MERDEKA - Norkumala Dewi; Rizki Gagah Perkoso; Supriadi; Dedy Hartanto; Hediati Mahardika; Widyatmike Gede Mulawarman; Akhmad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the readiness of teacher human resources in implementing the Merdeka Curriculum using a SWOT Analysis approach. Employing a descriptive qualitative method, data were collected through in-depth interviews, structured observations, and document analysis across several schools that have adopted the curriculum. The findings reveal that teachers possess notable strengths in professional motivation, pedagogical experience, and collaborative practices. However, significant weaknesses were identified in digital literacy, differentiated instruction, and the application of formative assessment. Externally, substantial opportunities arise from government policy support, digital learning platforms, and expanding professional learning communities, while threats include technological disparities, resistance to change, and administrative workload. The SWOT Analysis provides a strategic mapping indicating that teacher capacity-building should focus on enhancing digital competence, strengthening pedagogical mentoring, and leveraging external opportunities. This study concludes that the successful implementation of the Merdeka Curriculum depends on the synergy between teachers’ internal readiness and sustainable external support mechanisms.